Knowledge, Attitudes, and Practices of Residents in Patient Training at Tabriz University of Medical Sciences, Northwestern Iran - Amirala Aghbali; Sepideh Vosough Hosseini; Maryam Janani; Ali Fakhari; Khadijeh Abdal; Hadi Noori; Mahdi Vahidpakdel (Tabriz University of Medical Sciences, 2014)
Introduction: The aim of this study was to assess the knowledge and skill of clinical residents in Tabriz University of Medical Sciences, northwestern Iran, (as the future specialists), as well as their attitudes on the necessity of patient education, and the practice and responsibility of the residents in this field. Methods: Knowledge, attitudes, and practices of a random selection of 380 clinical residents at Tabriz University of Medical Sciences were assessed in 2011 through a comprehensive questionnaire about education. The data were analyzed using SPSS software.Results: There was no significant relationship between the two variables of sex and study period and the knowledge variable during the residency. However, there was a significant positive correlation between knowledge and age variables (P<0.05). The level of knowledge rose with aging because the amount of the model significance was less than0.05. Besides, the coefficient of sex was positive by regression analysis. There was no significant relationship between the previous variables and attitude variable. No significant relationship was seen between the previ¬ous variables and practice variable. Conclusion: The influence of age, sex, and year of study was apparent in the knowledge of the residents, but no considerable influence was shown in their practices and attitudes. Some educational strategies are needed to improve the practices and attitudes of the training group.